Higher Education Transformation: To what direction? (A Look at the transformation of Ar-Raniry State Islamic University) - Muluk, Safrul; Habiburrahim, Habiburrahim (SCAD Independent, 2018)
Service delivery in public institution has been one of the most important areas of management. Is it so important that an institution is often valued for its service delivery. Ar-Raniry State Islamic University was transformed from an Institute into University status in 2013. This transformation comes with an array of requirement and responsibilities that must be undertaken by its leaderhips. This article examines several crucial areas of management that often influence the quality of service delivery, especially at the Higher Education institution. Factors that often lead to either a success or a failure of an institutions, such as governance, leadership, and administration will also be discussed.